DINAMIKA KELOMPOK DAN PENINGKATAN KESEJAHTERAAN: KAJIAN PEMBERDAYAAN KELOMPOK USAHA MERICA MAJU JAYA DI DESA, MOWILA KEC. MOWILA, KAB. KONAWE SELATAN - Ramdani, Sitti; Juhaepa, Juhaepa; Tawulo, Megawati Asrul (Universitas Halu Oleo, 2020)
This research was conducted in Mowila Village, Mowila District, Konawe Selatan Regency. This research aims to dig deeper about the real form of efforts to improve the social welfare of farmers through pepper business groups. The method used is purposive sampling. The informants in this study involved pepper farmers as members of the Maju Jaya farmer group with 10 informants. Data collection using observation techniques, in-depth interviews, and study of documentation and data analysis was done in a qualitative description. The results of this study indicate that (1) Efforts to Increase Social Welfare of Farmers Through the Merica Business Group, Mowila Village, Mowila District, South Konawe Regency believe: (a) Providing understanding and employment opportunities for disadvantaged people in the world of work. (b) Encouraging and guiding farmers to be able to work together in business in groups. (2) Supporting factors and inhibiting factors of the Mowila Village's advanced pepper business group: (a) Supporting Factors, namely (1) Cooperation (2) Motivation, (3) Being transparent and trusting between related parties. (b) Inhibiting factors, namely (1) Lack of Capital Assistance. (2) limited ingredients to manage pepper. (3) The relationship is not good between members causing boredom that.